Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1186/1477-5751-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between sCTLA-4 levels in human plasma and common CTLA-4 polymorphisms

Abstract: Background: Cytotoxic T lymphocyte antigen-4 (CTLA-4) is an important downregulatory molecule expressed on both T and B lymphocytes. Numerous population genetics studies have documented significant associations between autoimmune diseases and single nucleotide polymorphisms (SNPs) within and around the CTLA-4 region of chromosome 2 in man. Furthermore, circulating levels of a soluble form of CTLA-4 (sCTLA-4) have been reported in a variety of autoimmune mediated diseases. Despite these findings, the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
(37 reference statements)
3
12
2
Order By: Relevance
“…Thus, our data do not support a relationship between these tested SNPs and circulating levels of CTLA-4 in the presence or absence of autoimmune disease. These results are in agreement with the study of Berry et al (2008), who found no statistically significant differences in observed versus expected genotypic frequencies for these SNPs when comparing positive versus negative blood levels of sCTLA-4.…”
Section: Ajbbsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, our data do not support a relationship between these tested SNPs and circulating levels of CTLA-4 in the presence or absence of autoimmune disease. These results are in agreement with the study of Berry et al (2008), who found no statistically significant differences in observed versus expected genotypic frequencies for these SNPs when comparing positive versus negative blood levels of sCTLA-4.…”
Section: Ajbbsupporting
confidence: 92%
“…It is thus not surprising that genetic variation within this region is implicated in susceptibility to autoimmune disease (Berry et al, 2008). The association of autoimmune diseases with the CTLA-4 locus could represent the effects of any of these three genes alone or in combination due to linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a significant correlation of the two SNPs in 3 0 UTR of the CTLA-4 gene, which were shown to be in strong linkage disequilibrium (32) (20,25) did not observe any relation between CT60 polymorphism and serum sCTLA-4 level. We did not report any significant correlation of other CTLA-4 gene polymorphisms studied with sCTLA-4 level in serum; however, we noted that promoter polymorphism (g.319COT) tended to be associated with higher sCTLA-4 levels.…”
Section: Discussionmentioning
confidence: 68%